OF THE PÁRAMO I COME PHOTO ESSAY ON WALKING, MEDITATING AND PHILOSOPHIZING IN THE VENEZUELAN ANDES (Isagoge - Journal of Humanities and Social Sciences, 2023)
In the strictest present, a fragmentary and interwoven essay between Mérida and Trujillo (Venezuelan Andes), trying to play the parodoja of writing...in a country exhausted by its situation. Characters and stories with all truth. There is no control of times and ages. Pact of nostalgia between narration and photographs. We try to harmonize what we learn from others with what we carry within us: pre-judgements of research methodologies and teacher training. From the wasteland I come passing a scriptural and tnográfíca voice and minimum that of meaning to the meditative and philosophical thought. We have tried to treat carefully the trans philosophy and decolonial projects in the trans methodical research in teacher training.
Keywords: Páramo; Parodox; Scriptural